MOTIVASI ORANG TUA DALAM MENGIKUTI PROGRAM TAMAN PENITIPAN ANAK (DAY CARE) BAGI ANAK USIA DINI - Yudi, Dede (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
TPA (Day Care) is a vehicle for educational services and fostering the welfare of children who serve as surrogate families for a period of time for parents unable or do not have enough time in educating and raising children because of work or other reasons. In the current era, a woman does not only deal with private or domestic sphere, but also the public sphere also he should be doing. It is a trend in urban areas. Due to the demanding needs of both to seek knowledge, seek income, or as a form of self-actualization, then they were expected to be more intelligent memenej various things that can be run both roles proportionally and professionally.Activities outside the parent is not a barrier to provide a complete service for children, therefore the presence of TPA (Day Care) felt very useful for parents, so that this phenomenon is becoming a trend. Besides the concerns of parents with children left at home by a baby sitter, given the recent flare once the parents of children abused by caregivers themselves. So even an accomplice, for parents who are well educated, they are worried to leave him with them, for the care and nurturing of children must necessarily who understand child development.The presence of TPA is legal there. In the education system in Indonesia, the presence of TPA has a clear legal basis in the 1945 Child Protection Act No. 23 of 2002, as well as the National Education Law No. 20 of 2003. TPA is one form of early childhood education in non-formal channels.